2019
DOI: 10.3390/agronomy9110750
|View full text |Cite
|
Sign up to set email alerts
|

Soil Physical Properties Spatial Variability under Long-Term No-Tillage Corn

Abstract: Spatial variability of soil physical and hydrological properties within or among agricultural fields could be intrinsically induced due to geologic and pedologic soil forming factors, but some of the variability may be induced by anthropogenic activities such as tillage practices. No-tillage has been gaining ground as a successful conservation practice, and quantifying spatial variability of soil physical properties induced by no-tillage practices is a prerequisite for making appropriate site-specific agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
2
15
0
1
Order By: Relevance
“…This field also had the highest standard deviation (SD) for mean yield and mean ECa. The variability in ECa and potato tuber yield could be due to intrinsic and extrinsic sources, including the weather, natural variation in soil (Awal et al, 2019) and crop management practices across the fields (Cemek, GüLer, Kiliç, Demir, & Arslan, 2007). These results also reflected the effect of temporal dynamics on the measured parameters due to sampling of ECa at different times during the study period (Farooque et al, 2012).…”
Section: Statistical Evaluation Of Thementioning
confidence: 82%
See 1 more Smart Citation
“…This field also had the highest standard deviation (SD) for mean yield and mean ECa. The variability in ECa and potato tuber yield could be due to intrinsic and extrinsic sources, including the weather, natural variation in soil (Awal et al, 2019) and crop management practices across the fields (Cemek, GüLer, Kiliç, Demir, & Arslan, 2007). These results also reflected the effect of temporal dynamics on the measured parameters due to sampling of ECa at different times during the study period (Farooque et al, 2012).…”
Section: Statistical Evaluation Of Thementioning
confidence: 82%
“…The sustainable use of soils depends on the management tools available to farmers (Keesstra et al, 2016;Lotter, Seidel, & Liebhardt, 2003;Pradhan, Fischer, Van Velthuizen, Reusser, & Kropp, 2015). This is possible through adopting precision agriculture practices that allow for site-specific management of crop fields with modern technologies capable of assessing soil variability and monitoring crop yield (Adamchuk, Hummel, Morgan, & Upadhyaya, 2004;Awal et al, 2019;Neupane & Guo, 2019;Perron et al, 2018). By contrast, conventional farming practices may limit crop yield below its potential values, compromise product quality, cause environmental degradation and reduce farm income through excessive applications and losses of agrochemicals (Corwin & Lesch, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…MI has undoubtedly proven to be an appropriate measure to assess the spatial dependence of soil properties [30,31]. Before a spatial inferential analysis, it has become routine to do an exploratory analysis of the variables involved in the modeling process; this usually involves calculating the MI but using the response variable as descriptive statistics prior to spatial modeling or a spatial interpolation process [32]. However, in our research, we found that the application of MI on a response variable in an exploratory way evidencing spatial dependence did not guarantee that this was precisely the result when this variable was incorporated into the modeling, because precisely the effect of the blocking can remove such dependency, something that was not observed before modeling where it had not been blocked.…”
Section: Resultsmentioning
confidence: 99%
“…La Dr, el co y la pt tuvieron un rango mayor a 75 m y un grado de dependencia espacial (gde) de cero (tabla 3) clasificado como débil acorde con Vidana, Biswas y Strachan [40], quienes clasificaron el gde como la relación entre el efecto pepita y la meseta expresado en porcentaje (<25 % débil; 25-75 % moderado; y >75 % fuerte), lo cual hace suponer que, hasta esa distancia, estas variables son espacialmente dependientes y poseen una baja relación entre los puntos de muestreo. Una situación similar de gde moderado fue reportada por Alvarado y su equipo y Guatibonza y sus colaboradores para la Dr [26], [27].…”
Section: Análisis Geoestadísticounclassified